2016
DOI: 10.1139/cjz-2015-0242
|View full text |Cite
|
Sign up to set email alerts
|

Muscle protection during hibernation of Daurian ground squirrels (Spermophilus dauricus): role of atrogin-1, MuRF1, and fiber-type transition

Abstract: We investigated the mechanism of protection from skeletal muscle atrophy in the hind limb extensor digitorum longus (EDL) muscle in hibernating Daurian ground squirrels (Spermophilus dauricus (Brandt, 1843)). The effects of unrestrained hibernation and 14-day hind limb-unloading on EDL were studied in three seasons, Summer, Autumn, and Winter. Atrogin-1 and MuRF1 mRNA skeletal muscle expression, wet muscle mass, and muscle-to-body weight ratios were unchanged during hibernation in all three seasons.EDL mass me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…In our previous studies, it has been reported that the phosphorylation levels of AKT and mTOR, two proteins related to protein synthesis, decreased significantly during hibernation in SOL, suggesting inhibition of protein synthesis during hibernation. The mRNA expression of atrogin‐1 and MuRF1, two proteins related to protein degradation, remained unchanged during hibernation in both skeletal muscles, indicating unaltered protein degradation during hibernation (Dang, Feny, et al, ; Dang, Li, et al, ). Therefore, the inhibition of protein synthesis during hibernation may be the main reason of vacuolation in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, it has been reported that the phosphorylation levels of AKT and mTOR, two proteins related to protein synthesis, decreased significantly during hibernation in SOL, suggesting inhibition of protein synthesis during hibernation. The mRNA expression of atrogin‐1 and MuRF1, two proteins related to protein degradation, remained unchanged during hibernation in both skeletal muscles, indicating unaltered protein degradation during hibernation (Dang, Feny, et al, ; Dang, Li, et al, ). Therefore, the inhibition of protein synthesis during hibernation may be the main reason of vacuolation in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%